Epoxy-based thermally conductive adhesives with effective alumina and boron nitride for superconducting magnet. (10th November 2020) - Hwang, Young Jin; Kim, Jun Min; Kim, Lee Su; Jang, Jae Young; Kim, Myungsu; Jeong, Sooyeol; Cho, Jung Young; Yi, Gi-Ra; Choi, Yeon Suk; Lee, Gaehang
Abstract: Heat management is one of the key technologies for reliable and high-performance electric devices. We have developed thermally conductive adhesives based on a commercial thermally conductive epoxy, Stycast 2850FT (S2850), with an additional unfilled resin and boron nitride (BN). The optimal mixing ratio of BN to epoxy resin was 10 wt%, and the thermal conductivity (κ) of this mixture was 1.65 W/m·K at 25 °C, 1.6 times higher than that of S2850. Such enhancement of κ may be attributed to the formation of more thermal conductive paths generated by the effective additives inside the composite adhesive layers, which was confirmed with elemental mapping analysis. Our epoxy-based thermally conductive adhesives with improved κ was then implemented for a superconducting magnet. Because of the enhanced heat dissipation of our composite adhesive, the superconducting magnet showed enhancement of 42.7%, 14.8%, and 76.6% in the cooling rate, the minimum quench energy, and the normal zone propagation velocity in the longitudinal direction at 70% of the current-carrying capacity, respectively, which are important parameters in the operational performance of a superconducting magnet, compared to a coil with S2850. Graphical abstract: Image 1